Noninvasive ventilation in hypoxemic respiratory failure - Raja Dhar; Dipansu Ghosh; S Krishnan (The Journal of Association of Chest Physicians, 2016)
Noninvasive ventilation (NIV) refers to positive pressure ventilation delivered through a noninvasive interface (nasal mask, facemask, or nasal plugs) etc. Over the past decade its use has become more common as its benefits are increasingly recognized. This review will focus on the evidence supporting the use of NIV in various conditions resulting in acute hypoxemic respiratory failure (AHRF), that is, non-hypercapnic patients having acute respiratory failure in the absence of a cardiac origin or underlying chronic pulmonary disease. Outcomes depend on the patient's diagnosis and clinical characteristics. Patients should be monitored closely for signs of noninvasive ventilation failure and promptly intubated before a crisis develops. The application of noninvasive ventilation by a trained and experienced team, with careful patient selection, should optimize patient outcomes.